Extraocular Myocysticercosis Involving Levator Palpebrae Superioris-Superior Rectus Complex: A Rare case Report - Ansari, Sajid; Gupta, Mukesh Kumar; Ahmad, Kaleem; Dhungel, Kanchan; Kumar, Abhishek; Rauniyar, Raj Kumar (Asian Journal of Medical Sciences, 2013)
The ocular involvement of the cysticercosis is a rare entity involving eyelids, extraocular muscles, orbit, conjunctiva, anterior chamber, uvea, retina, vitreous and optic nerve. All the extraocular muscles are involved in myocysticercosis. Ultrasonography and Computed tomography are the imaging modalities for evaluation of ocular cysticercosis. The patients can be treated with systemic steroids and albendazole; however surgical excision is the treatment of choice. We report a rare case of extraocular myocysticercosis in nine years old boy diagnosed on ultrasonography and computed tomography. Asian Journal of Medical Science, Volume-4 (2013), Pages 36-39 DOI: http://dx.doi.org/10.3126/ajms.v4i4.8163